2016
DOI: 10.5812/pedinfect.35730
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Laboratory Characteristics of Pediatric Campylobacter spp. Acute Gastroenteritis

Abstract: Background: Although Campylobacter strains are one cause of acute bacterial gastroenteritis, their clinical and laboratory findings have only been examined in a few studies. Objectives: This study was performed to evaluate the frequency level as well as the clinical and laboratory findings of patients with acute gastroenteritis caused by Campylobacter. Patients and Methods:In this cross-sectional study, 419 Iranian children in Semnan city with acute gastroenteritis were assessed for their clinical and laborato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
(28 reference statements)
0
9
0
Order By: Relevance
“…A questionnaire and a consent form were provided to the parents, guardians and/or patients. The two main inclusion criteria were as follows: 1) completion of the consent form; and 2) direct observation of over five white blood cells per high-power microscope field (HPF) in a diarrhea sample 7. None of the patients had taken antibiotics in the week before hospitalization.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A questionnaire and a consent form were provided to the parents, guardians and/or patients. The two main inclusion criteria were as follows: 1) completion of the consent form; and 2) direct observation of over five white blood cells per high-power microscope field (HPF) in a diarrhea sample 7. None of the patients had taken antibiotics in the week before hospitalization.…”
Section: Methodsmentioning
confidence: 99%
“…Although studies have found different frequencies and different Shigella species from north and south Iran,7–9 most reported phenotypic criteria such as frequency and antibiotic resistance profiles. In addition, Iran is a huge country with different climates in different geographical regions.…”
Section: Introductionmentioning
confidence: 99%
“…In Central Iran, 33% (76/230) diarrheal stools from children were PCR positive for C. jejuni in 2015, among which most of the infections occurred in the age group of 1-3 years (Rastyani et al, 2015;Abbasi et al, 2019). Campylobacter infection was found to be more prevalent in girls in Semnan, contrary to that of Central Iran (Mazaheri et al, 2016;Abbasi et al, 2019).…”
Section: Iranmentioning
confidence: 97%
“…The detection rates of C. jejuni in diarrheal patients from Mazandaran and East Azerbaijan in 2017 and 2016 were reported to be 27% (20/74) and 27.8% (62/223), respectively (Ranjbar et al, 2017;Divsalar et al, 2019). Mazaheri et al reported that in Semnan between 2014 and 2015, Campylobacter was isolated from stools of 8.6% (36/419) of children (1-12 years old) with diarrhea; children in age group 6-12 years were found to have the highest frequency of positive cultures (Mazaheri et al, 2016). Around the same time between 2013-2014 in Hamadan, 10% (12/120) of the diarrheal stool samples from children less than 10 years old had Campylobacter isolated.…”
Section: Iranmentioning
confidence: 99%
See 1 more Smart Citation